Towards lead-free all-inorganic perovskite solar cell with theoretical efficiency approaching 23%. (6th December 2022) - Alla, Mohamed; Bimli, Santosh; Manjunath, Vishesh; Samtham, Manopriya; Kasaudhan, Abhishek; Choudhary, Ekta; Rouchdi, Mustapha; Boubker, Fares
ABSTRACT: Single junction solar cells with organic-inorganic perovskites have achieved efficiency > 25%, yet they suffer from long-term durability and toxicity. Additionally, all the best-performing perovskite light harvesters contain lead, hindering their real-time application. Herein, we report preliminary studies with the SCPAS-1D software package on three different perovskite light harvesters, namely FAPbI3, FASnI3, and CsSnI3, considering an approach towards stable and environmentally benign perovskite light harvesters. Additionally, to extract the best performance, each perovskite light harvester is analysed with four electron transport layers, namely TiO2, SnO2, BaSnO3, and La doped BaSnO3 . The physical parameters such as thickness, doping, and defect density are optimised for the subsequent films to deliver high performance. Further, the operating temperature-dependent variation in power conversion efficiency and other solar cell parameters are also analysed. In an attempt to replace the high-cost gold counter electrode, a comparative study on the performance of other possible counter electrodes is also comprehensively detailed.